HRAS, EGFR, MET, and RON Genes Are Recurrently Activated by Provirus Insertion in Liver Tumors Induced by the Retrovirus Myeloblastosis-Associated Virus 2 - Pecenka, Vladimir; Pajer, Petr; Karafiat, Vít; Kasparova, Petra; Dudlova, Jana; Dvorak, Michal (Journal of virology, 2017)
Myeloblastosis-associated virus 2 (MAV-2) is a highly tumorigenic simple avian retrovirus. Chickens infected in ovo with MAV-2 develop tumors in the kidneys, lungs, and liver with a short latency, less than 8 weeks. Here we report the results of molecular analyses of MAV-2-induced liver tumors that fall into three classes: hepatic hemangiosarcomas (HHSs), intrahepatic cholangiocarcinomas (ICCs), and hepatocellular carcinomas (HCCs). Comprehensive inverse PCR-based screening of 92 chicken liver tumors revealed that in ca. 86% of these tumors, MAV-2 provirus had integrated into one of four gene loci: HRAS, EGFR, MET, and RON Insertionally mutated genes correlated with tumor type: HRAS was hit in HHSs, MET in ICCs, RON mostly in ICCs, and EGFR mostly in HCCs. The provirus insertions led to the overexpression of the affected genes and, in the case of EGFR and RON, also to the truncation of exons encoding the extracellular ligand-binding domains of these transmembrane receptors. The structures of truncated EGFR and RON closely mimic the structures of oncogenic variants of these genes frequently found in human tumors (EGFRvIII and sfRON).IMPORTANCE These data describe the mechanisms of oncogenesis induced in chickens by the MAV-2 retrovirus. They also show that molecular processes converting cellular regulatory genes to cancer genes may be remarkably similar in chickens and humans. We suggest that the MAV-2 retrovirus-based model can complement experiments performed using mouse models and provide data that could translate to human medicine.
Keywords: kur domácí; insertional mutagenesis; geny erbB-1; avian retroviruses; Proviruses; hemangiosarkom; ptačí proteiny; Genes, erbB-1; Chickens; Proto-Oncogene Proteins c-met; protoonkogenní proteiny c-met; Hemangiosarcoma; Carcinoma, Hepatocellular; cholangiokarcinom; Avian Proteins; Avian Myeloblastosis Virus; virus ptačí myeloblastózy; Cholangiocarcinoma; Carcinogenesis; Virus Integration; Animals; lidé; Oncogenes; proviry; inzerční mutageneze; zvířata; onkogeny; tyrosinkinasové receptory; Humans; karcinogeneze; hepatocelulární karcinom; integrace viru; Receptor Protein-Tyrosine Kinases; Liver Neoplasms; nádory jater; Mutagenesis, Insertional; retroviral oncogenesis